Factors contributing to E-learning success in Nigeria institutions of higher learning - Atanda, Balogun Naeem; Ahlan, Abdul Rahman (IIUM Press, 2017)
In 2013, out of the 1.7 million students that sat for Unified Tertiary Matriculation Examination (UTME) in Nigeria, less than five hundred thousand (29.4%) can have a placement in the Nigeria Institutions of Higher Learning. Perhaps, people are thinking of an alternative to the conventional university programs which accommodates less than the students willing to benefit from education, and eLearning is seen as a solution to this issue of students’ placement. However, implementation eLearning does not guarantee success. This study investigates factors contributing to eLearning success in Nigerian Institutions of Higher Learning. In addition, the study also developed a model that can be used to measure eLearning success. This study investigates the factors contributing to eLearning system success from the users’ perspectives. Many factors may influence Information Systems success, this study only focus on individual trait which comprise of human personality trait and infrastructural capability. Personality trait such as extraversion, emotional stability and openness are important traits that are investigated, likewise the influence of other contributing factors such as the infrastructural capabilities which include computer ownership, energy generation and internet access are discussed. An explanatory mixed methods design using survey and an open-ended interview as the data collection methodology was used as the research design for the study. A survey using questionnaire provided quantitative descriptions of the sample within the chosen population through a data collection while a follow-up process was conducted using an unstructured one-on-one open-ended interview to collect relevant data. The study found the contributing factors to play role on the success of the eLearning in Nigeria and the study shows success in the eLearning program within the institutions of higher learning. The finding of the study paves a way for other research that will involve developed countries as well. This allow the intended eLearners to identify their personality trait before considering eLearning as an option as well as their infrastructural capability, likewise the Institutions of Higher Learning can suggest intended learners to be able to cater for their infrastructure before enrolling. Researchers will benefit from the eLearning success model and also the findings attached to the research that considers the individual trait to the success of an Information Systems.